Effect of respiratory muscle endurance training on performance and respiratory function in professional cyclists during the off-season - Rehor, A.; Novotný, J.; Bernaciková, M.; Paludo, A. C. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: The study aimed to analyze the effect of respiratory muscle endurance training (RMT) on performance and respiratory function in professional road cyclists during the off-season period. METHODS: Twenty professional road cyclists from the Czech Republic were divided into the control (CON) (N.=10) and the RMT (N.=10) groups. Cyclists from the RMT group accomplished 30 sessions over 10 weeks. Performance in the incremental cycling test and respiratory capacity via test were assessed before and after 10 weeks in both groups. The comparison between and within the groups was performed, together with effect size and delta % (P<0.05). RESULTS: Significant effects on respiratory function during the exercise, on lung volume utilization at 90% of VO2max (TV-90%) and maximal voluntary ventilation (MVV) were found in RMT compared to the CON group, with a moderate effect size (0.71 and 0.61), and improvements of 13% and 14%, respectively. Parameters of performance in the cycling protocol and respiratory function at rest presented better values in the RMT group, however with no significance and in minor magnitude. CONCLUSIONS: Using RMT during off-season benefits professional road cyclists by improving the major efficiency of respiratory function during progressive efforts. Therefore, the protocol of RMT could be used as an ergogenic aid during this period in order to maintain respiratory adaptations, optimizing the pre-season training. Adjustments can be made to improve the parameters outcomes.